Ethnobotanical survey of medicinal plants used to treat inflammatory conditions in the Sétif Region (Algeria) - Saoudi, Soulef; Bentahar, Assia; Mayouf , Nozha; Barghout, Nihed; Tadrent, Wafa; Bettihi, Sara; Ben Latreche, Dounia Zad; Nouioua, Wafa; Djidel, Saliha; Bouaziz, Amel; Dahamna, Saliha; Khennouf, Seddik (Ethnobotany Research and Applications, 2026)
Background: Despite significant advances in the pharmaceutical industry, traditional herbal medicine remains a major therapeutic resource in many regions. In Algeria’s Sétif province, medicinal plants are widely used to treat inflammatory diseases. However, specific ethnobotanical knowledge regarding inflammatory conditions in this high-plateau region remains under-documented. Methods: An ethnobotanical survey was conducted using a structured questionnaire administered to 107 informants, including herbalists, patients, and regular users of medicinal plants. Data were collected on sociodemographic characteristics, plant species, plant parts used, preparation methods, and treated diseases. Ethnobotanical indices (Relative Frequency of Citation, Family Importance Value, and Informant Consensus Factor) were calculated, and Correspondence Analysis was performed. Results: A total of 26 medicinal plants from 14 families were documented. Women comprised most users (68.22 %), with the 20–30 years age group most represented (43.9%). Leaves were the most used plant part (34.2%), infusion the predominant preparation method (56.41%), and oral administration the most common route (62.94%). Respiratory disorders were the most frequently treated (24.29%). Origanum vulgare L. ssp. glandulosum had the highest RFC (0.224), while Zingiberaceae exhibited the highest Family Importance Value (FIV = 0.175). The highest ICF was recorded for musculoskeletal conditions (0.878), followed by neurological (0.857) and infectious (0.821) disorders. Conclusions: This study highlights the enduring importance of herbal medicine in the Sétif region and reveals a rich diversity of plants used for inflammatory conditions. High consensus for musculoskeletal and neurological disorders reflects well-established ethnomedical knowledge. Highly cited species warrant phytochemical and pharmacological validation, providing a baseline for future research and underscoring the need for sustainable harvesting. Keywords: Ethnobotanical survey, inflammatory diseases, Medicinal plants, Sétif region, Algeria.